Verbal fluency as a measure of lexical access and cognitive control in bilingual persons with aphasia. Issue 11 (1st November 2020) - Carpenter, Erin; Rao, Leela; Peñaloza, Claudia; Kiran, Swathi
ABSTRACT: Background : Lexical access in bilinguals can be influenced by the demands that different interactional contexts pose on cognitive control processes. However, how varying cognitive control demands impact lexical access in bilingual persons with aphasia (BPWA) remains unclear. Verbal fluency tasks may provide valuable insights into the interplay between cognitive control and lexical access in BPWA by addressing word generation abilities in language contexts that exert varying degrees of cognitive control effort. Aims : The present study aimed to examine the performance of BPWA on a semantic category generation task that required word retrieval in single and dual-language contexts under varying cognitive control demands and a traditional letter fluency task conducted in single-language contexts. We also examined the associations between verbal fluency performance and (i) bilingual language history, and (ii) performance on standardized language assessments in both BPWA and healthy bilinguals. Methods and Procedures : Thirteen Spanish-English BPWA and twenty-two Spanish-English healthy bilinguals completed a language use questionnaire, verbal fluency testing and standardized language assessments in each language. The semantic category generation task included four conditions: two conditions examined word retrieval in the first-acquired (L1) and second-acquired language (L2) in single language contexts (No Switch-L1 and No Switch-L2) and two conditions elicited word retrieval in dual-language contexts (Self-Switch and Forced-Switch) with low and high cognitive control demands by allowing or restricting switching across languages. The letter fluency task was administered in single language contexts only (F, A, S for English and P, M, R for Spanish). Verbal fluency performance was compared across conditions and groups using multivariate analyses. Further, correlational analyses were used to examine associations between verbal fluency tasks and bilingual language history, language assessments, and cognitive function. Outcomes and Results : Overall, the healthy bilinguals produced a higher proportion of accurate words in both verbal fluency tasks relative to the BPWA. Results indicate that BPWA were more sensitive to the effects of increased cognitive control on lexical access relative to healthy bilinguals. BPWA and healthy bilinguals' performance on both verbal fluency tasks was associated with metrics of bilingual language history and standardized language assessments. Additionally, for BPWA, L2 letter fluency performance was associated with cognitive function. Conclusion : Our findings suggest that verbal fluency tasks can help characterize the impact of cognitive control on lexical access in BPWA in single and mixed language contexts with important clinical implications.